2018
DOI: 10.1590/0104-1428.04917
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization, thermal and mechanical behavior of oligosebacate plasticized poly(lactic acid) films

Abstract: ObstractThe biodegradable aliphatic oligoester oligo(trimethylene separate) (OTS) was synthesized by polycondensation and used to plasticize poly(lactic acid) (PLA). Casting films of PLA and PLA/OTS with concentrations of 1, 5 and 10 wt.% were prepared, and these films were characterized by thermal analyses, crystallinity, rheology and mechanical tests. DSC revealed the decrease in the T g of PLA films with addition of the oligomer and a partial immiscibility. Addition of OTS to PLA slightly decrease the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
5
0
2
Order By: Relevance
“…In the case of E2MP ligand, a sharp peak was observed at 1731 cm −1 , which can be assigned to C=O stretching. The sharp peak at 1177 cm −1 corresponds to C−O stretching vibrations of C−C(C=O)‐O group . The C−H stretching vibrations were observed at 2983 and 2936 cm −1 .…”
Section: Resultsmentioning
confidence: 84%
“…In the case of E2MP ligand, a sharp peak was observed at 1731 cm −1 , which can be assigned to C=O stretching. The sharp peak at 1177 cm −1 corresponds to C−O stretching vibrations of C−C(C=O)‐O group . The C−H stretching vibrations were observed at 2983 and 2936 cm −1 .…”
Section: Resultsmentioning
confidence: 84%
“…It also explains the temperature range (88–98°C) of weight loss, which is higher than the boiling point of chloroform (60°C). [ 48 ] The thermogram clearly defines the degree of degradation of PLA and PLA‐MSW blends.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that all PBSe spectra showed similar absorption peaks. The absorptions at 2930 cm −1 and 2852 cm −1 were assigned to the symmetrical and the antisymmetric stretching vibration of methylene groups in the polyester structures (−CH 2 ), respectively [ 50 , 51 ]. The intensity of these two bands was greater for the PBSe samples with a higher Se content in their composition.…”
Section: Resultsmentioning
confidence: 99%